2016
DOI: 10.3389/fmed.2016.00052
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Factor XII during Inflammatory Reactions

Abstract: The contact system was originally identified as an obsolete part of the coagulation system, but it has been repeatedly implicated in inflammatory states, such as infection, as well as in allergic- and chronic inflammatory disease. Under these conditions, there is surprisingly little evidence that factor XII (FXII) acts as a coagulation factor, and its activity appears to be mainly directed toward activation of the kallikrein–kinin system. The contact system factors interact with pathogens as well as cells of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
(54 reference statements)
1
16
0
1
Order By: Relevance
“…Studies proposed that depending on the mode of activation, FXII can either trigger blood coagulation via activation of FXI or activate the kallikrein‐kinin system (KKS). When FXII is bound to an activating surface, the classic activation, FXII is cleaved and activated by plasma prekallikrein/kallikrein in complexing with high molecular weight kininogen (HK) which subsequently leads to FXIa generation . In addition, enveloped viruses were shown to enhance intrinsic pathway activation in vitro .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies proposed that depending on the mode of activation, FXII can either trigger blood coagulation via activation of FXI or activate the kallikrein‐kinin system (KKS). When FXII is bound to an activating surface, the classic activation, FXII is cleaved and activated by plasma prekallikrein/kallikrein in complexing with high molecular weight kininogen (HK) which subsequently leads to FXIa generation . In addition, enveloped viruses were shown to enhance intrinsic pathway activation in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, enveloped viruses were shown to enhance intrinsic pathway activation in vitro . However, FXII can also be activated by an alternative mechanism via proteases, including elastase and plasmin . Certain bacteria were shown to express specific LPS, polyphosphates, elastase, or plasminogen activators to trigger bradykinin production via FXII activation .…”
Section: Introductionmentioning
confidence: 99%
“…These experiments suggest that the activating cleavage site after R353 is shielded from cleavage. These findings indicate a two-step mechanism in which FXII-T309K is first truncated, exposing R353 for subsequent cleavage by PKa, as we previously proposed [15]. 3 The proline-rich region of FXII contains naturally occurring cleavage sites for a variety of enzymes, including neutrophil elastase and cathepsin K. These enzymes are unable to directly activate FXII.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither paper definitively demonstrates that bradykinin is a critical disease mediator in human FXII-HAE patients during a real-world angioedema attack. Fortunately, recent clinical studies have demonstrated that this is most probably the case: both infusion of additional C1INH and B2R inhibition are therapeutic in FXII-HAE patients [7].In our review, we propose that plasmin makes a significant contribution to bradykinin C1INH-HAE and FXII-HAE; firstly, levels of plasmin-a2-antiplasmin complexes are elevated during swelling attacks [8,9]. Secondly, there is a growing body of biochemical evidence for a role of plasmin as activator of the contact system [6,10,11] More convincingly, there good clinical experience with tranexamic acid as a maintenance therapy in both forms of HAE [7,12,13], and even in patients with (H)AE of unknown origin [14].…”
mentioning
confidence: 84%
“…In our review, we propose that plasmin makes a significant contribution to bradykinin C1INH-HAE and FXII-HAE; firstly, levels of plasmin-a2-antiplasmin complexes are elevated during swelling attacks [8,9]. Secondly, there is a growing body of biochemical evidence for a role of plasmin as activator of the contact system [6,10,11] More convincingly, there good clinical experience with tranexamic acid as a maintenance therapy in both forms of HAE [7,12,13], and even in patients with (H)AE of unknown origin [14].…”
mentioning
confidence: 99%